Ogniska zakażenia pochodzenia zębowego u chorych kardiologicznych = Dental focal infections in patients with cardiac issues - Anna Janas; Adam Chiżyński; Aleksandra Szczepkowska; Anna Olborska; Piotr Osica (Kazimierz Wielki University, 2015)
Janas Anna, Chiżyński Adam, Szczepkowska Aleksandra, Olborska Anna, Osica Piotr. Ogniska zakażenia pochodzenia zębowego u chorych kardiologicznych = Dental focal infections in patients with cardiac issues. Journal of Education, Health and Sport. 2015;5(1):75-87. ISSN 2391-8306. DOI: 10.5281/zenodo.14049 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A75-87 https://pbn.nauka.gov.pl/works/528333 http://dx.doi.org/10.5281/zenodo.14049 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2014. Revised 05.10.2014. Accepted: 25.12.2014.   Ogniska zakażenia pochodzenia zębowego u chorych kardiologicznych Dental focal infections in patients with cardiac issues   Anna Janas1, Adam Chiżyński2, Aleksandra Szczepkowska2, Anna Olborska2, Piotr Osica2   1 Zakład Stomatologii Ogólnej UM w Łodzi 2 Zakład Chirurgii Stomatologicznej UM w Łodzi   Adres do korespondencji: dr n. med. Piotr Osica Zakład Chirurgii Stomatologicznej UM  w Łodzi 92-213 Łódź, ul. Pomorska 251 e-mail: pioosica@interia.pl   Praca finansowana przez Uniwersytet Medyczny w Lodzi w ramach działalności statutowej nr 503/2-163-01/503/01.   Streszczenie Spośród chorób układu krążenia, które mogą mieć związek z ogniskami zapalnymi w jamie ustnej na szczególną uwagę zasługuje infekcyjne zapalenie wsierdzia (IZW). Celem pracy było wykazanie ognisk zakażenia pochodzenia zębowego u chorych kardiologicznych, Materiał i metody. Badaniem retrospektywnym  objęto 103 pacjentów (42 kobiety i 61 mężczyzn), leczonych w Zakładzie Chirurgii Stomatologicznej UM w Łodzi, z powodu ognisk zakażenia pochodzenia zębowego, w okresie od 1 października 2010 roku do 20 listopada 2014 roku. Wiek chorych wahał się od 32 do 68 lat.  U wszystkich pacjentów w procedurach chirurgii 1- dnia usunięto ogniska zakażenia pochodzenia zębowego. Pacjenci stosowali doustne antykoagulanty. Wyniki. Oceniano ryzyko przedłużających się krwawień poekstrakcyjnych  u leczonych  osób. Wśród 55 chorych, którzy stosowali doustne antykoagulanty brak krwawienia wtórnego po wykonanym zabiegu   stwierdzono u 45 chorych, u których wskaźnik INR wahał się od 0,9 do 2.  Natomiast u 10 osób stwierdzono mały stopień krwawienia wtórnego w drugim dniu zabiegu u 6 chorych, a w 4 przypadkach w trzecim dniu po zabiegu.  Na późniejsze wystąpienie krwawień wpłynęło przerwanie terapii przeciwzakrzepowej i obniżenie wskaźnika INR do 1,8. Wniosek. Konieczne jest zwrócenie szczególnej uwagi u osób kardiologicznych na profilaktykę stomatologiczną.       Słowa kluczowe: zębopochodne ogniska zakażenia, choroby serca.   Abstract Among cardiovascular diseases that may be linked to the dental focal inflammations, endocarditis deserves substantive attention. The aim of the article was to demonstrate dental focal inflammations in patients with cardiac issues. Material and methods. Retrospective study included 103 patients (42 women and 61 men), treated in Department of Oral Surgery of Medical University in Lodz, due to dental focal infections, between the 1st of October 2010 and 20th of November 2014. The age of the patients varied - from 32 to 68 years. The whole group was subjected to elimination of the dental infections in procedures of 1 day surgery. Patients received oral anticoagulants. Results. The risk of prolonged post-extraction bleeding has been assessed. Among 55 anti-coagulant treated patients, no post-operative bleeding has been ascertained in 45 cases, in which the preoperative INR ranged from 0,9 to 2. Whereas in 10 cases the bleeding was described as oozing and occurred in 6 patients in second day after the surgery and in 4 in the third day. Withdrawal of anticoagulant therapy caused the postoperative bleeding and reducing the INR to 1.8. Conclusion Special considerations regarding the patients who receive the anticoagulant therapy and undergo dental surgery are needed.   Key words: dental focal infections, cardiovascular diseases.